Developing a Program for Contaminated Site Management in Low and Middle Income Countries - Kovalick, Walter W., Jr. (World Bank Group, Washington, DC, 2014)
Contaminated sites associated with economic growth and development and increased urbanization pose a growing public health and environmental problem. Emissions and discharges, particularly uncontrolled ones, onto land can pollute the soil and the groundwater beneath, and can also affect surface water quality and sediments in nearby rivers and streams. This document is intended to summarize the rationale and the major policy, regulatory, implementation, and organizational issues involved in creating a contaminated site program, especially for low and middle income countries. The document offers alternatives regarding the design and implementation of such a program. It provides an action agenda of short- and longer-term activities to be considered when establishing a contaminated site program. In addition to providing some optional approaches for the many policy and programmatic issues, the document provides numerous references from the experience of other country programs to draw upon in considering program options. The document is intended to help support World Bank staff or other international financial institutions and assistance agencies in their dialogues with governmental officials in low and middle income countries regarding specific options and steps on developing or implementing contaminated sites programs in their countries. It is also relevant for governmental agencies in these countries responsible for site contamination and pollution management, land use planning, and site development at local and national levels. The document is organized in the following chapters: chapter one gives introduction. Chapter two is setting policy and legislative framework which highlights the development of policy and legislative purpose, principles, strategy and design, and related legislation. Chapter three is regulatory issues which presents major topics that may be the subject of regulations by a ministry or agency. Chapter four is contaminated site program management which presents management, organizational, and operational issues, including issues of coordination and partnerships within branches of government and with other stakeholders. Chapter five is action agenda for contaminated site program which provides the development of an action agenda of short- and longer-term actions to be considered in forming a contaminated site program, including creation of a national management plan for contaminated sites.